Features of Leaf Area Index Spatial Distribution in XiŽan Using Landsat TM Images - Zhou, Jie; Jiang, Jianjun; Zhang, Li; Wu, Hongan; Zhang, Hailong (MTT, 2005)
Leaf area index (LAI) is an important ecological parameter. The radiation intensity of Landsat TM/ETM represents the reflectivity of different canopy on the ground, which has a closer relation with leaf area index (LAI). In this paper, Landsat TM/ETM data were used to retrieve canopy reflectivity of Xi an region in 1998, 2000, and 2003 by 6S model respectively. By correlation analysis of canopy reflectivity, vegetation index (VI) obtained from remote sensing data and field measurements of LAI; a reasonable retrieval model for LAI was established, that is 6911 . 0 * 4967 . 6 + = NDVI LAI . Unlike the former research that digital number (DN) of images was usually used to retrieve LAI, in this study, ground canopy reflectivity was used. Theoretically, canopy reflectivity changes according to LAI condition, and it has physical meaning. Based on this, the spatial distribution of LAI in 1998, 2000 and 2003 was retrieved and its feature was also analyzed.
Keywords: Ys; leaf area index (LAI); vegetation index; 6S model; spatial distribution